Black Women and the Pandemic Imagination: Pedagogy as a Rehearsal of Hope During Covid-19 - Brown, Kimberly Nichele (Radical Teacher, 2022)
This article discusses Brown’s use of Afrofuturism and critical pedagogy in her creation of the class, Black Women and the Pandemic Imagination (BWPI), which she taught in Spring 2021 at Virginia Commonwealth University. Brown explains her implementation of precarious pedagogy to attend to the affective needs of students struggling under the effect of Covid-19. She discusses how the analytics of Afrofuturism and critical pedagogy provide strategies for combating white supremacy and for promoting social justice. Brown demonstrates how reading theoretical works by black women about cataclysmic moments (i.e., the apocalypse, contagions, pandemics and even the Middle Passage), as well as studying representations of black women during these moments provides an opportunity for students to “rehearse hope.” Brown sees BWPI as a course premised on Black Lives Matter and committed to black futurity – “there are black people in the future.” Through BWPI, she hoped to ignite the radical imagination of her students, thereby empowering them to think about creating a more equitable future.